Budaya Tam Uim Reu (Masuk Rumah Adat) dalam Penanganan Pasien Patah Tulang di Rumah Adat Babafa, Desa Umutnana, Kecamatan Sasitamean, Kabupaten Malaka - Assit, Aprilia Fransiska Karunia; Romeo, Petrus; Takaeb, Afrona E. L. (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
The culture of Tam Uim Reu (entering the traditional house) is a fracture treatment performed inside the Babafa Traditional House, Umutnana Village, Sasitamean Sub-district, Malaka Regency. The purpose of this study is to explore the culture of Tam Uim Reu in the treatment of fracture patients. This type of research is qualitative research with an ethnographic approach. The number of informants in this study were 4 people, including fracture healers, Babafa traditional spokespersons, fracture patients who have used Tam Uim Reu cultural treatment, and local health workers. The results showed that fracture treatment in this culture is carried out in the traditional house by giving Queen Wilhelmina's guilder coins as a condition of entry. After entering the traditional house, the patient is cleaned according to custom, then gives some money to the fracture shaman to get traditional medicine to treat the fracture. Fracture patients should bring along blood relatives to assist the traditional healer during treatment. During the treatment, the patient must abide by the taboos and prohibitions according to the prevailing customs. The treatment is carried out by Tatobi (warm water compress) on the fracture wound, the impact is to reduce pain and swelling, then Tam Uim Reu cultural fracture medicine is applied, when doing Tatobi, using the medium of chopped luan banana (Musa Paradisiaca) stems, the banana sap functions as an antioxidant to help close the wound, then using bamboo as a support tool to reposition the broken and displaced bones. After the treatment is complete and the fracture patient has recovered, the fracture patient and the fracture shaman must hold a traditional procession to thank the ancestors for the healing obtained, after which the patient can leave the traditional house and rest at home